Zinc and potassium priming of maize (Zea mays L.) seeds for salt-affected soils. (27th July 2020) - Basit, Ammara; Hussain, Shahid; Abid, Muhammad; Zafar-ul-Hye, Muhammad; Ahmed, Niaz
Abstract: Soil salinity and sodicity are major limiting factors in crop production globally. Priming with osmolytes has been proposed to mitigate the negative effects of these limiting factors. However, most of the priming studies have been conducted in hydroponics and only limited information is available regarding the impacts of seed priming in natural soil conditions. In the present study, untreated and primed (with distilled water, 4 mM ZnSO4 and 23 mM K2 SO4 ) seeds of maize were grown in pots filled with a saline soil or a saline-sodic one. In the saline and saline-sodic soil, ZnSO4 priming increased the shoot dry biomass of 30-day-old plants by 38 and 69%, and the root dry biomass by 22 and 48%, respectively, when compared to the controls. Water priming (hydro-priming) was also effective in the saline soil, increasing shoot dry biomass by 28% over the control values. In both soils, ZnSO4 priming increased significantly the shoot Ca and Zn concentrations, whereas it decreased shoot Na concentrations. Moreover, ZnSO4 priming increased leaf chlorophyll contents and photosynthesis rates over those in the controls. Priming treatments, especially with water and ZnSO4, also increased significantly the shoot K/Na, Ca/Na, and Mg/Na concentration ratios. In conclusion, priming with ZnSO4 may improve shoot growth in both soils, whereas water priming was suitable for the saline soil.